SISTEM PENENTUAN BESARNYA PUNGUTAN DARI HUTAN ALAM (Royalty system of Natural Forest) - Apul Sianturi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The significant contributions of the natural forest to the well being of Indonesian Society in these decades can not be denied. This fact is a major incentive in managing natural forest in sustainable basis.One of the tools that can be used to sustain natural forest is eficient use of natural resources, which could be done by imposing proper royalty system. By collecting royalty base on the utilized logs, the loggers tend not to utilize margin timber as applied nowadays.Since the royalty is not part of the timber cost anymore if the payment system takes place after the timber sale, the royalty should be higher. than the payment before timber sale where royalty is a part of timber cost. The difference is in the margin of risk and profit. Far this purpose this study tries to build a model that can be used to determine the price of the royalty that should be paid by the loggers for each of the payment system.The result of the model shows that stumpage price (royalty) paid by the loggers in these days should be increased, especially if the payment based on utilized logs.In order to increase eficiency of timber utilization the payment of stumpage price should be based on volume which is taken from timber stand, at least based on volume of timber which is cut in the forest.